Respuesta :

Answer:

[tex]y = -4[/tex]

Step-by-step explanation:

Given

[tex](x_1,y_1) = (0, -4)[/tex]

[tex](x_2,y_2) = (5, -4)[/tex]

Required

Determine the equation

First, calculate the slope using:

[tex]m = \frac{y_2 - y_1}{x_2 - x_1}[/tex]

[tex]m = \frac{-4 - (-4)}{5 -0}[/tex]

[tex]m = \frac{-4 +4}{5}[/tex]

[tex]m = \frac{0}{5}[/tex]

[tex]m = 0[/tex]

The equation is then calculated using:

[tex]y = m(x -x_1) + y_2[/tex]

This gives:

[tex]y = 0(x - 0)-4[/tex]

[tex]y = 0-4[/tex]

[tex]y = -4[/tex]